Importance of Investors’ Sentiment Where Significance of Micro and Macro Variables is Low for Building Trading Strategy - Sen, Partha (Indian Journal of Research in Capital Markets, 2016)
Many important variables are common to analysts for pricing of listed stocks in different buy or sell side institutions and brokers. These common variables are payout, revenue, profit, dividend, leverage, profit/dividend growth, and macro variables like industrial index, foreign investment, prime lending rate, exchange rate, and so forth. Since the 1970s, these variables have beenÂ ubiquitous in research. These are effective, but the importance of investor sentiment related to announcement and understanding of behavioral finance are reflecting in trading desks now. Sentiment of investors was traced long back, but it has not been explored or documented well. Significance of the behavior along with quantitative numbers for building trading strategies is the focus of this paper. Observation of the sentiment or behavioral aspect of stock price can help analysts predict valuation more accurately. Future research in this subject is catching attention, but it is still in an early phase, so this opens immense scope of projection and recommendation accuracy in equity research. The present research paper is based on the research conducted in the third quarter of financial year 2015-2016 with a data set from the financial years 2001 to 2015.